POLA KEMITRAAN DAN PENDAPATAN USAHATANI KELAPA SAWIT: KASUS KEMITRAAN USAHATANI KELAPA SAWIT ANTARA PT PERKEBUNAN NUSANTARA VII UNIT USAHA BEKRI DENGAN PETANI MITRA DI DESA TANJUNG JAYA, KECAMATAN BANGUN REJO, KABUPATEN LAMPUNG TENGAH - Pasaribu, Agustina Irene; Hasanuddin, Tubagus; Nurmayasari, Indah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This research aims to determine the institutional system in the management of oil palm farming partnership implementation, determine the implementation of partnerships between PTPN VII and oil palmfarmers, and analyze the financial feasibility of oil palm farmers who involvein the partnership in Tanjung Jaya Village of Bangun Rejo District, Lampung Tengah Regency. The study was conducted inTanjung Jaya Village of Bangun Rejo District, Central Lampung Regency.Based on the age of plants, 36 famers wererandomly selected as respondents from 46 farmers who joined the partnership. The research data were analyzed using Gross B/C, Net B/C, NPV (Net Present Value), IRR (Internal Rate of Return), and PP (Payback Period). The results showed that institutional system in the management of oil palm farming andthe implementationof partnership between PTPN VII and farmers was operated effectively both in personnel and systems of norms, as well as the physical equipment. Implementation of the partnership was a core-plasm partnership. The company served as a capital lender, in the form of ready planted oil palm seedlings, and accompanied by technical guidances and counseling in the form of direct guidance on planting, maintenance, and good harvesting. Cultivation of oil palm by farmers who joined the company was financially viable to be developed, had a Gross value of B/C equal to 1.6616; Net B/C 1.9519; NPV 27383347.824; IRR 23.71%, and PP of 9 years. Key words: financial feasibility, institutional system, oil palm farming, partnership